Produksi Perdagangan dan Peredaran Produk Teripang di Kota Sorong Papua Barat Daya - Gulam Arafat; Hapsari Puspitaningtyas, Indrie; Indah Kintani, Novia (Jurnal Riset Perikanan dan Kelautan, 2024)
Sea cucumber is one of marine biota that have an ecologically important role in the waters and have high economic benefits as food and medicinal ingredients. This affects the high level of market demand so that fishermen make sea cucumber as the main target of catches. Sorong city is one of the entrances and exits of the trade of fishery products from the island of Papua, so that a study is needed related to the potential of sea cucumber in this area. This study aims to give an overview of production, trade and circulation sea cucumber to input and evaluation policy in management for the utilization of the sea cucumber. Methods used is descriptive of quantitative and qualitative methods. Based on the data, information was obtained among others identified 6 genera of sea cucumber that are traded, namely Bohadschia, Holothuria, Pearsonothuria, Thelenota, Stichopus, dan Actinopyga, which the genus Holothuria dominated approximately 34.88% of the total amount of products in distribution. Amount of sea cucumber products in Sorong city is around 20 tons/year with economic potential in the form of state income reaches Rp.44.000.000. The sea cucumber that comes from Sorong city are distributed to the Surabaya city which is one of the doors to export fisheries products abroad